Comparison of ReLu Activation and Logistics Functions in Classification of Casting Product Defects with Perceptron Multilayer Approach - Apriyandi M; Muhamad Fatchan; Suratman (International Journal of Integrated Science and Technology, 2024)
In the industrial sector, production quality is very important for company operations and must be managed effectively. ISO 9001 emphasizes quality management to direct processes and improve organizational efficiency. Quality control is important to prevent defects in materials, because foundry production must produce high quality materials so that they can be used in the long term. ISO 14001 environmental management environment, with high output impacts on the environment due to lack of transparency. This research uses ReLu and Logistics Activities to improve casting quality using multilayer perceptron technology, finding that ReLu activities have a higher dominance (99%) compared to other actives.